The effect of health promotion in overcoming dengue hemorrhagic fever in public senior high school one Bitung city, North Sulawesi, Indonesia - Engkeng, Sulaemana; Punuh, Maureen Irinne; Asrifuddin, Afnal (International Journal Of Community Medicine And Public Health, 2021)
Background: Dengue hemorrhagic fever is a health problem in Indonesia because both the virus that causes it and the mosquitoes that transmit it are widespread in residential areas and public facilities throughout Indonesia. This study aims to determine the level of knowledge before and after counselling. Methods: The type of research used is quantitative research with a quasi-experimental approach in one group pre-test post-test which was held at State high school 1, Bitung city. The population in this study were all students at the State high school 1, Bitung city with a total sample of 89 students using the Lemeshow formula. The sampling technique used was stratified random sampling with the inclusion criteria being willing to be respondents and being present at the time of the research, while the exclusive criteria were transfer students from other schools. Results: Based on the results of the study, it was found that there was an increase in respondents' knowledge about dengue prevention. The results of the analysis of student knowledge in the pre-test showed mean=13.17 with a standard deviation of 1.848 and in the post-test showed mean = 16.08 with a standard deviation of 2.341. There is a significant increase in knowledge of student's knowledge with the results obtained, namely the difference in the mean of -2,910 and p<0.05. Conclusions: The outcomes achieved by the counselling given to students can provide increased knowledge through the media of posters, stickers, brochures, videos and banners.